Our Experience in Comparing Laparoscopic and Open Herniotomy For Pediatric Inguinal Hernia Repair: Revisiting the Debate - Khanna, Sanat Kumar; Ankit,; MAHESHWARI, SAURABH (Iranian Journal of Pediatric Surgery, 2023)
Introduction: Traditionally, open groin exploration has been done for congenital inguinal hernia and hydrocele, but recently, laparoscopic herniotomy has gained popularity and has become a successful alternative to open herniotomy. This study compares Laparoscopic herniotomy [LH] and Open herniotomy [OH] regarding operative time, patency of contralateral internal ring, post-op complications, recurrence rates, and parental satisfaction. Materials and Methods: A multicentric randomized prospective comparative study was done at two tertiary care centers in North India. A total of 180 patients (newborn to 12 years) with congenital inguinal hernia and congenital hydrocele were included based on the inclusion criteria and were randomized using computer-generated numbers to assign to open and laparoscopic herniotomy surgery groups. Various parameters were evaluated during the pre-op, intra-op, and post-op periods. Results: The study was carried out from Nov 2014 to April 2019. The majority of the patients operated on had a right inguinal hernia in both groups (50% in each group). For bilateral inguinal hernia or hydrocele mean time taken by open technique was 41.16 minutes, and by laparoscopy was 37.75 minutes. In the case of unilateral hernia/hydrocele, it was 20.24 minutes by open technique compared to 24.3 minutes by laparoscopy. But the difference in operative time was statistically not significant. Conclusion: Based on our observation and results, we conclude that both laparoscopic and open techniques are equally effective and comparable in managing inguinal hernia and hydrocele, with advantages and disadvantages. Claims of one procedure being better than the other and counterclaims of one being more complicated than the other are ill-founded, and the efficacy of each procedure must be viewed with an unbiased approach.